PENGUATAN NILAI KARAKTER KEMANDIRIAN DALAM PEMBELAJARAN TEMATIK MELALUI BLENDED LEARNING DI KELAS V - Hafizd Sholehudin; Bistari Bistari; Siti Halidjah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
Abstrak:This study aims to describe the value of the character of independencethrough Blended learning in the VD class of the Pontianak MujahidinElementary School. This study uses a qualitative approach and the typeof research used is descriptive. The subject in this study was a VDclass teacher at the Pontianak Mujahidin Elementary School. Data wascollected by using observation, interview, and documentationtechniques. The results of this study are as follows: (1) The lesson planfor the VD class teacher of the Pontianak Mujahidin ElementarySchool already contains several elements of self-reliance. Even theRPP also shows an effort to instill the value of independence throughBlended learning in tamatic learning. The values of self-reliancecharacter in RPP are self-confidence, responsibility, discipline,sharing. (2) The implementation of learning the value of independencehas been applied in thematic learning in the VD class of the PontianakMujahidin Elementary School. The values of independence that areimplemented in the implementation of thematic learning are selfconfidence, responsibility, discipline, and sharing. (3) The obstaclesfaced by the VD class teacher of the Pontianak Mujahidin ElementarySchool are the internet signal network constraints of students whocarry out online learning and the short time allocation. Based on theresults of the study, increasing the value of the character ofindependence through Blended learning has been implemented well,although there are some obstacles in learning through blended learningin thematic learning.Keywords :Blended learningelementary school,value of independent character